DEVELOPMENT OF A WEB-BASED TONSEA LANGUAGE CORPUS USING THE EVOLUTIONARY PROTOTYPING METHOD - Conggresco, Sherly; Rantung, Vivi P.; Kainde, Quido C. (Informatika, Universitas Jenderal Soedirman, 2024)
Without realising it, when humans increasingly follow technological advances and are only concerned with the demands of the times where technology can coexist with humans, humans sometimes forget to preserve their culture, one of which is local language. One of them is Tonsea language. Tonsea language is a regional language originating from North Sulawesi. The purpose of this study is to research material for Tonsea language corpus linguistics in the preparation of dictionaries and add Tonsea language resources to preserve the Tonsea language by developing a website to analyse the Tonsea language corpus. Corpus analysis can also be used to research or study variations in the use of the Tonsea language because the corpus can help linguists and lexicographers in the preparation of dictionaries in working on dictionary microstructures which include lemmas/sublemmas, word classes, definitions and writing. As a result, there are six key concepts of corpus analysis techniques, namely tokens, word frequency, concordance, collocation, ngrams, and word lists. In the Token feature, the Token can be used by pekamus to create a dictionary and linguists can also analyse the Tonsea language on Ankorsea and for the Concordance, Collocation and Ngram features users can search for keywords to find out the meaning of the use of a language. This research uses the Evolutionary Prototyping method.